For a Psychosocial Approach to Decent Work - Pouyaud, Jacques (Frontiers in Psychology, 2016)
The notion of decent work was developed by the International Labour Organization twenty years ago. The notion is now well known by lawyers, economists, and sociologists, and even if it appears difficult to define it clearly, it constitutes a useful general framework with which to think of the relationships between policy practices, work market globalization, and human rights principles. The fields of career guidance and counseling psychology are highly concerned by questions of social justice and human rights that people experience through work. Career choices being made in a liquid and unstable society, incompatibility between individualist values and collective work issues, increasing psychological health problems at work, work-family balance in precarious job situations, the growing necessity of mobility, adaptability or flexibility… all of these questions are at the heart of current career counseling practices, and concern the decent work debate. Nevertheless, the notion of decent work is not well developed in the field of vocational psychology. Despite its relevance, it is difficult to operationalize the policy and human rights principles during career counseling sessions. The article aims to explore the usefulness of the concept for career counselors, and to propose a psychosocial framework that incorporates decent work in career counseling practices. The first part of this article presents the theoretical bases of the notion of decent work and their possible use in the field of psychology. It deals with the necessity of a multilevel and psychosocial perspective, that takes into account both objective and subjective dimensions of decent work. The second part focuses on a case study illustrating how the notion of decent work emerges during counseling sessions. Four levels of the work experience linked with subjective and objective dimensions of decent work are explored; the personal level, the activity level, the collective level, and the social level. Finally, the third part discusses and proposes a framework based on the analysis of the four dimensions of work (activity, trade, others and society) in order to integrate a psychosocial view of decent work into career counseling.